Characterization of the preferences towards jalapeño peppers from the perspective of the Sonoran consumers (Agro Productividad, 2021)
Objective: To assess the Sonoran (Mexico) consumer perspective regard their buyinghabits, consumption and the attitudes and attributes they most valued from jalapeñopepper.Design / Methodology / Approach: The assessment took place in three phases. Thefirst consisted of the design of a questionnaire, the second its application to a sample ofn = 200 consumers and finally univariate (means and modes) and bivariate (Chi-square)analyzes on the obtained data.Results: The flavor is a key element in the consumption of jalapeño peppers. There is atendency towards frequent consumption, although the portions are measured since theyare usually less than 0.5 kg. It was identified that for the consumer it is important nodamage or browning is visible on the external appearance of the peppers, and that theyprefer peppers of a dark green color over another coloring. Specifically, there is awillingness to pay between $ 0.5 and $ 1.0 US per kilo. The frequent consumers ofjalapeño pepper are under 40 years old, accentuated in the 18 to 24 years old segment,with medium income level. In this segment, there is the preference for aroma andhotness (pungency) that the chili peppers have.Study limitations / implications: This study is limited to consumers from thenorthwestern region of Mexico. The obtained information provides guidelines to deepenthe knowledge of this product from their market perspective. The added- valuestrategies should be aimed to increase the external quality of the product.